The Legal Review of Telecommunications Central Construction of Joint Venture Cooperation Form - Avrila Anzani (Universitas Islam Sultan Agung, 2023)
The cooperation in this case a Joint Venture is one of the investment activities with the concept of joint ventures with local investors in the agreement of a business will do. In business, every company will review the business opportunities that can be expanded to achieve its business goals. In this case, there are limited human resources which are obstacles to the implementation of the business. Thus, there are several companies cooperate with foreign parties in the form of joint venture cooperation. The research method used a normative juridical approach with primary and secondary legal concepts which are then analyzed by statutory approach and historical approach. The researcher collects data sources based on statutory provisions as primary materials and secondary legal materials, the researcher obtains secondary legal materials through literature in books, journals, research reports, and articles. The joint venture which is the status of Foreign Investment, then the percentage of shares follows the requirements regulated in the Law. There are several agreements which include License Agreements, Loan Agreement, Employment Agreement, and other Agreements. As with the regulations described above, it can be interpreted that the establishment of a joint venture company is based on a review of the negative investment list in terms of foreign investment. Several things should be of concern, that is the negative investment list in Presidential Regulation No. 49 of 2021 concerning Amendments to Presidential Regulation Number 10 of 2021 concerning the Investment Business Sector which regulates that business fields are closed to domestic and foreign. In share sharing, there is capital that have to be met as the basic capital for the establishment of a corporation PMA, that is having an investment value of more than IDR 10,000,000,000.00 (ten billion rupiahs) excluding land and buildings. Then regarding the investment done with the establishment of a capital partnership corporation the founders, in this case the party conducting the joint venture, have to be established by 2 or more people and have to take each of their shares by the agreement.